The importance of hypoxia sensors in detecting HIF-1 biomarker at high altitude - Shaharuddin, Shazreen; Nik Abd Rahman, Nik Mohd Afizan; Masarudin, Mas Jaffri; N Alamassi, Mohammedarfat (MedCrave Group, 2023)
The episode of prolonged exposure to high altitude can cause hypoxia and potential significant health consequences. In people with high altitude disorder, the body reaction to high altitudes starts with the formation of a protein called hypoxia-inducible factor (HIF), which triggers a series of other physiological changes and plays a central role in the hypoxia response; its activity is regulated by the oxygen-dependent degradation of the HIF-1α protein. This deserving condition provides an opportunity to study the effect of low oxygen tension of flying at high altitude that could lead to hypoxia using hypoxia sensor.